Anthropometric indices in a community‐dwelling Australian population aged 70–90 years: The Sydney Memory and Ageing Study. Issue 1 (11th September 2014) - Arcot, Jayashree; Kim, Jihee; Trollor, Julian; Brodaty, Henry; Crawford, John; Sachdev, Perminder
Abstract Aim To evaluate the anthropometric indices in community‐dwelling people aged 70–90 years in Sydney, Australia. Method Cross‐sectional data were collected during the Sydney Memory and Ageing Study from two federal government electoral areas from 2005–2007. Participants with no dementia were recruited to the study (n = 1037). The anthropometric parameters including body weight, standing height, waist circumference and hip circumference were obtained with the average participation rate of 97%. The study population was then stratified by gender and age groups. Results With increasing age, the body weight and standing height decreased, while waist circumference and waist to hip ratio showed different patterns. With reference to the World Health Organization classification for body mass index, overweight and obesity were found in 75.3% of men and 61.2% of women. In particular, the result revealed that 23% of the study cohort was obese. While all men had mean waist to hip ratios exceeding the cut‐off value (≥0.90), only 53.7% of women were categorised as having a condition leading to increased risk of mortality (≥0.85). The mean waist to hip ratio in men and women was 0.96 ± 0.06 and 0.86 ± 0.07, respectively (±standard deviation). Conclusions This study provides gender‐ and age‐specific distributions for six anthropometric measurements for older Australians to identify individuals with potentially greater risk of disease. Overweight and obesity are common in the older population. However, more data from across Australia are needed to confirm the findings from this study.